2019
DOI: 10.4049/jimmunol.1801448
|View full text |Cite
|
Sign up to set email alerts
|

Graft γδ TCR Sequencing Identifies Public Clonotypes Associated with Hematopoietic Stem Cell Transplantation Efficacy in Acute Myeloid Leukemia Patients and Unravels Cytomegalovirus Impact on Repertoire Distribution

Abstract: Although the impact of donor graft composition on clinical outcomes after hematopoietic stem cell transplantation (HSCT) has been studied, little is known about the role of intragraft gd TCR repertoire on clinical outcomes following HSCT. Using a highthroughput sequencing platform, we sought to analyze the TCR g-chain (TRG) repertoire of gd T cells within donor stem cell grafts and address its potential impact on clinical response in the corresponding patients. A total of 20 peripheral blood stem cell grafts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 57 publications
(107 reference statements)
5
37
1
Order By: Relevance
“…The studies included in the qualitative synthesis highlighted that the Vd1 subtype mediates the antiviral effect 31,32,38,48,51 and that distinct gd T-cell clones are important in control of viral infection (Table 1). 12,45 The OS and DFS follow-up period were not consistently reported among the studies, ranging from 2, 7 2.5, 54 3, 5,56 4, 53 and 5, 55 up to 7 years. 4 Only 1 study reported HR between high vs low gd T-cell groups 4 ; for all the others, we estimated the HR following standard guidelines.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The studies included in the qualitative synthesis highlighted that the Vd1 subtype mediates the antiviral effect 31,32,38,48,51 and that distinct gd T-cell clones are important in control of viral infection (Table 1). 12,45 The OS and DFS follow-up period were not consistently reported among the studies, ranging from 2, 7 2.5, 54 3, 5,56 4, 53 and 5, 55 up to 7 years. 4 Only 1 study reported HR between high vs low gd T-cell groups 4 ; for all the others, we estimated the HR following standard guidelines.…”
Section: Resultsmentioning
confidence: 93%
“…Two qualitative studies also described that gd T-cell clonotypes were associated with less relapse after HSCT (Table 1). 45,47 Only 1 study assessed the gd T-cell graft composition and observed no effect on relapse incidence (RR, 0.99; 95% CI, 0.76-1.29; P 5 .95). 53 The pooled risk effect of both immune reconstitution and graft content further confirmed improved outcome for patients with high gd T cells (RR, 0.65; 95% CI, 0.42-1.29; P 5 .05), although there was evidence of subgroup heterogeneity (I 2 5 81.2%, P 5 .02).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no public or shared sequences specific to CMV, as individual patients had distinct clonal γδ TCR responses to CMV, although there was some homology . Another study also showed that the TRD repertoire had reduced diversity in patients with CMV, further demonstrating the remarkable impact CMV can exert on γδ T cells …”
Section: Evidence For γδ T Cells In Favorable Outcomes Following Tranmentioning
confidence: 99%
“…59 Another study also showed that the TRD repertoire had reduced diversity in patients with CMV, further demonstrating the remarkable impact CMV can exert on cd T cells. 60…”
Section: Nkg2a Ligandsmentioning
confidence: 99%